The Effect of TED-Ed Animated Videos on Senior High School Students’ Listening Skills - Fatimah Maharani; Wiwiet Eva Savitri (Jurnal Pendidikan dan Sastra Inggris, 2026)
Listening skills play a primary role in the ability to communicate in a foreign language. While previous studies have demonstrated the benefits of TED-Ed animation-based media, few have examined the impact of its interactive features: Think, Dig Deeper, and Discuss on listening skills, especially in Indonesian senior high schools. This study analyzed the use of TED-Ed videos and these features to improve listening skills. A quasi-experimental design with pre-test and post-test was applied to 72 eleventh-grade students, divided into experimental and control groups. Data were collected through a listening comprehension test and analyzed using an independent sample t-tests. The findings revealed a statistically significant difference in listening comprehension between the groups, with the experimental group outperforming the control group (M: 92.14 vs. M: 85.42. Furthermore, the effect size analysis revealed a large effect (Cohen’s d = 1.66), indicating a significant impact of TED-Ed’s interactive features on students’ listening skills. These findings suggest that integrating the Think, Dig Deeper, and Discuss activities into TED-Ed videos can effectively improve listening comprehension by encouraging active engagement and deeper processing of audiovisual content in English as a foreign language classrooms.